Joint effort among research infrastructures to quantify the impact of plastic debris in the ocean. (22nd May 2019) - Conchubhair, Diarmuid Ó; Fitzhenry, Deirdre; Lusher, Amy; King, Andrew L; van Emmerik, Tim; Lebreton, Laurent; Ricaurte-Villota, Constanza; Espinosa, Luisa; O'Rourke, Eleanor
Abstract: Marine debris is one of the most significant problems facing the marine environment, endangering wildlife, polluting oceans and is an issue which holds global significance. Plastics constitute a large proportion of marine debris, and their persistence can cause a number of negative consequences for biota and the environment, including entanglement and ingestion, which can lead to mortality. Most plastics never biodegrade and instead break down into smaller pieces which are more difficult to monitor and eventually become so small (micro and nanoplastics), that they are challenging to observe or intercept in the ocean. Marine-based Research Infrastructures (RIs) monitor several environmental parameters and are situated around the globe; however, none of these are routinely monitoring marine debris or plastics. Currently, the only infrastructures in place with regard to marine debris are 'physical debris interception infrastructure' in the form of barriers constructed to prevent marine debris from entering the ocean. Several knowledge gaps and restraints exist within current in situ infrastructure including technological immaturity, diverse methodologies and lack of data harmonisation. Nevertheless, marine RIs could monitor microplastics within the water column on a long-term basis and initial steps towards developing technology are promising.